Peripheral osteoma of the maxilla: A rare case report - Kunal Sah; Alka Kale; H Seema; Vijaylaxmi Kotrashetti; B J Pramod (Wolters Kluwer Medknow Publications, 2011)
Osteoma is a benign osteogenic lesion with a very slow growth, characterized by proliferation of either cancellous or compact bone. Depending on its location, osteoma may be classified as central, peripheral or extraskeletal type. Although peripheral osteomas of the upper jaw are rare, diagnosticians can however encounter them in their clinical practice, which are probably misdiagnosed. These should be considered in the differential diagnosis of any slow-growing, non-tender, bony hard, non-compressible, non-fluctuant and non-pulsatile swelling present on the Oral and Maxillofacial region. We report a rare case of maxillary peripheral osteoma in a 50-year-old female patient. To best of our knowledge this is the eleventh case of maxillary osteoma reported in the English language literature.